LEGAL PROTECTION OF INDONESIAN LABOR IN MANAGEMENT OF HOUSEHOLD OVERSEAS - Arpangi Arpangi (Jurnal Pembaharuan Hukum, 2019)
Protection of Indonesian Migrant Workers abroad is regulated in Act number 18 of 2017 concerning the Protection of Indonesian Migrant Workers. Many Indonesian workers work abroad due to the explosion of a very high population, which triggers very high unemployment. This research uses library research (qualitative research) and is a qualitative, descriptive analysis. Literature research, which examines the number of literature relevant to the problem of this writing. Data analysis used in this study is descriptive qualitative by analyzing data/information obtained through descriptive research with library research which is then systematically compiled and described qualitatively. Suggestions that can be delivered related to legal protection according to Law No.18 of 2017 is to increase the guidance and counseling for Indonesian Migrant Workers who will work so that the Indonesian Migrant Workers are ready to be deployed. Based on article 88 of Law No. 18 of 2017 then the government should create a body as mandated by Law No. 18 of 2017 so that the protection of Indonesian Migrant Workers abroad can run effectively